The historical development of the commemoration of the June 16, 1976 Soweto students' uprisings: a study of re-representation, commemoration and collective memory - Hlongwane, Ali Khangela (My University, 2015)
South Africa’s post-apartheid era has, in a space of nearly two decades, experienced a massive memory boom manifest in a plethora of new memorials, monuments, museums and the renaming of streets, parks, dams and buildings. This memorialisation process is intrinsically linked to questions of power, struggles and contestation in the making and remaking of the South African nation. The questions of power, struggle and contestation manifest as a wave of debates on the place of history, collective memory, identity and social cohesion in the inception as well as the functioning of the various memorialisation projects in society. This thesis concludes that debates concerning the meaning(s) as well as the way in which the June 16, 1976 uprisings have been memorialized, has been ongoing for the last three decades, and will continue into the future. This, as the findings bear out, is because the wider contextual situating of collective memory in its intangible and tangible form is intrinsically linked to complex experiences of the past; to ongoing experiments of a “nation” in the making, as well as pressing contemporary social challenges. The thesis also concludes that questions of power, struggle and contestation also manifest as a quest for relevant idioms and aesthetics of re-representation and memorialisation. Further, the thesis makes observations on the politics behind the assembling and the assembled archive as a toolkit in the fashioning of pasts and the making of collective memory. It reflects on the processes of re-thinking and remaking of the June 16, 1976 archive. These conclusions have been arrived at through an investigation of how the memory and meaning of the June 16, 1976 uprisings have been re-constructed, re-represented and fashioned over the last three decades. This was done by tracking and analysing the complex, diverse forms and character of its memorialisation. In the process, the study arrives at a conclusion that the memorialisation of the June 16, 1976 uprisings is characterised by the multiplicity of tangible and intangible features. The intangible features are characterised by forgetting, at one level, and are, on another level, animated through rituals of commemoration, counter- commemoration and memorial debate. The memorial debate on the uprisings is that of unity and diversity, division, contestation and counter-commemoration and essentially irresolvable, as history and memory are tools to address contemporary challenges.
A THESIS SUBMITTED TO THE WITS SCHOOL OF THE ARTS, UNIVERSITY OF THE WITWATERSRAND, 2015
Keywords: June 16, 1976; uprisings; Soweto; nation-building; reconciliation; tourism; history; memory; counter-commemoration; commemoration; life histories; archive; youth; Black Consciousness; liberation struggle